A look at the bright side of dance: Analysis of the relationship between dance experience, experience quality, satisfaction and word of mouth - METIN ARGAN; SABRI KAYA; CANER OZGEN; GOZDE YETIM; ALIKHAN GUSEYNOV (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: Leisure experience, including dance motivation, is one of the key factors for participation in dance events or festivals. Therefore, the experience quality that facilitates individual relationships is likely to influence the dancers' participation. The purpose of this study is to determine and to analyze dance experience motivations, experience quality, satisfaction and word-of-mouth. Material and methods: The sample of this study consisted of 201 persons who attended the Turkey Dance Festival and who were selected by the convenience sampling method. In this study, the theoretical principles of structural equation modeling (SEM) were applied with the Amos 20 program to analyze the data. Results: The results showed that there were significant relationships (<0.05) between dance experience motivations, experience quality, satisfaction and WOM. This study results are important both as significant and practical implication for leisure managers' strategies regarding their leisure and experience motivation, and contribution to the leisure literature. Conclusions: The findings of this study can help event managers contribute to increased participation in sustainable dance practices, and the participant-based experience value can be used as a planning tool to attract the attention of event organizers. The findings of this study also give useful insights into theoretical, practical and managerial implications for dance event organization and provide suggestions for future research.